Kaolin in the diet and its effects on performance, litter moisture and intestinal morphology of broiler chickens - Marina Jorge de Lemos; Lígia Fátima Lima Calixto; Osvanira dos Santos Alves; Daniele Santos de Souza; Bárbara Brandt Moura; Túlio Leite Reis (Ciência Rural, 2015)
The objective of this study was to evaluate the effect of the addition of kaolin in the diet on performance, litter moisture and intestinal morphology of broiler chickens. Four hundred ninety-two broiler chickens distributed in a completely randomized design with three treatments and four replicates of 41 birds each, divided into three periods (15-21; 22-34; 35-52 days) were used. The following treatments were: Control - reference diet without added kaolin; treatment 1 - reference diet + 0.75% kaolin; Treatment 2 - reference diet + 1.5% kaolin. The variables analyzed were: feed intake, average weight, average weight gain, feed conversion, litter moisture, villus height and crypt depth. The inclusion of kaolin in the diet significantly reduced feed intake, increased weight and average weight gain and improved feed conversion of broilers. The litter moisture decreased significantly after the inclusion of kaolin in the diet. The height of the duodenal villi of broilers increased significantly after inclusion of kaolin, while crypt depth was not influenced. The inclusion 0.75% of kaolin in the diet improved the performance, decreased litter moisture and benefited the intestinal integrity of broilers.